Direct recycling of aluminium alloy 6061 and 7075 employing cyclic extrusion compression back pressure technique - Mohamad Syahmi, Shahrom (2016)
The direct recycling process is an alternative method of recycling waste of chip aluminium without melting the materials as compared to conventional recycling technique (secondary production). The cold compaction stage is the most crucial process of the direct recycling process. The billets density, b achieved through the cold compaction stage significantly influences the hardness (mechanical properties) and chip boundaries (microstructural properties). The problem of conventional compaction (direct compaction) presents low of b. The objective of this study is to develop the Cyclic Extrusion Compression Back Pressure (CECBP) technique to improve the b which influences the hardness and chip boundaries of aluminium alloy 6061 and 7075 chips in the direct recycling process. Taguchi Method was used as a tool to analyse and optimise the CECBP factors namely the pressure, P back pressure, Pb cycle time, tc and holding time, th. Different lubricant strategy techniques (flood, dry and minimum quantity lubricant (MQL) were used to obtain different types of aluminium chips. Conventional compaction (direct compaction technique) was used to get b value. The MQL showed the highest b results compared to flood and dry technique. The experimental results suggested that the CECBP technique is able to improve cyclic billets density cyb to 12.11% (AA6061) and 5.45 % (AA7075) compared to direct compaction technique. It is also established that the cyclic specimen hardness, Hcys and chip boundaries for both aluminium alloys improved when cyb value increased by using regression analysis. Pressure is identified to be the most significant factor in influencing the properties of cyb, cys and Hcys. In conclusion, CECBP technique had successfully improved the cold compaction stage for a direct recycling process and can used as direct recycling process of aluminium in industry.